How are the messages of the official grade ten sexuality education curriculum at a former model C girls' high school in South Africa mediated by student sexual cultures? - Mthatyana, Andisiwe Tutula Zinzi (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2014)
The increase in teenage pregnancy among school going learners is reported in the media as a crisis. Politicians and other stakeholders have also raised their views and concerns about pregnancy. In particular, these views and concerns perceive teenage pregnancy among school going learners as a cancer that needs a remedy because it has negative consequences for the learners, in particular the girl child. However, for all the sense of public crisis concerning sexuality and schooling, the voices of young people themselves regarding their own sexual subjectivity are seldom heard. This study focused on how girls in a former model C all girls high school negotiate and make sense of the meaning of the messages that they receive from the formal curriculum. The concept of student sexual cultures was employed in this study. Student sexual cultures are the informal groups that exist in the school and the girls take part in it. It is in these groups that the girls learn about sexuality and also make sense of their own gendered identities. This study employed ethnographic techniques of classroom observation coupled with in-depth interviews, focus groups and solicited narratives in order to understand how the participants experience and "take up" the messages they receive in the formal sexuality education component of the Life Orientation (LO) curriculum. The data was collected over a period of three months and was analysed using a directed content analysis. Four dominant themes emerged from the study. Firstly, the data reveals the school is a space of competing and conflicting discourses of sexuality and the learners are involved in a constant negotiation of the meanings of the messages. Secondly, the data shows the contested and confirmations of learners subjectivity. It shows that learners are regarded as sexual beings both in the formal and informal school cultures but there are limitations around one's sexual subjectivities. Thirdly, the data reveals that the school is a site in which a variety of femininities are reproduced, contested and struggled over. Femininities are constructed in the complex context of the school thus the school emerges as a site in which multiple femininities intersect with class, race and sexuality. Lastly, this study argues for the incorporation of the discourse of erotics in the formal curriculum which allows young people's voices to be heard. This approach (discourse of erotics) can be seen as a process of becoming, which focuses on possibilities of improving sexuality education as opposed to an imposed sexual model that is applied to young people and assumed to be the solution to young people's sexuality.
Keywords: Sex instruction -- South Africa; Sex instruction -- Cross-cultural studies; Teenage pregnancy -- South Africa; High school girls -- Sexual behavior -- South Africa; Multicultural education -- South Africa; Model C schools (South Africa); Girls' schools -- South Africa